An impact imaging method for monitoring on construction of immersed tube tunnel foundation treated by sand-filling method. (March 2019) - Che, Ailan; Zhu, Renjie; Fan, Yanmin; Feng, Shaokong
Highlights: Model of immersed tube tunnel foundation treated by sand filling was conducted. Relationship between P-wave response energy and diffusion radius is established. Spatiotemporal evolution law of sand foundation during sand filling was explored. P-wave impact imaging method can reliably monitor sand-filling state. Abstract: Sand filling method (sand-flow method) is widely used in the treatment of immersed tube tunnel foundation, but quick and reliable method for real-time monitoring on the formation of sand-deposit and the connection of sand-deposit between neighboring sand filling hole is absent. In this paper, a full-scale model of immersed tube tunnel foundation treated by sand filling method was conducted. The case was simplified as a multi-layered media problem, and a nondestructive testing method based on P-wave was explored to control the sand filling time in different hole. Through model testing, the relationship between the change rate of P-wave response energy and the radius of the sand-deposit is established. Kriging interpolation principle was employed to make a complete evaluation of the sand-deposit. The radius of sand-deposit measured by the P-wave impact imaging method (PII) agree well with the average radius observed by the observation window. Comparing the results of PII in sand filling hole with the relative compactedness of sand foundation after the sand filling, it can be found that the sand foundation boundary detected by PII method agree well with model test result, and the region with higher relative compactedness has a good correspondence with the regions with high change rate of PII. So, the PII method can detect the radius and the distribution of relative compactedness of sand-deposit. Because the method is convenient in calculation, the construction of sand filling foundation can be monitored in real time by PII method. In conclusion, the method can be used to monitor sand-filling treatment in immersed tube tunnel on real-time, and provide a scientific basis for the design and construction of immersed tube tunnel Engineering.